When the teacher's explanation matters: Students' opinions on university teaching (Revista Lusófona de Educação, 2026)
Recent transformations in higher education emphasise changes in traditional teaching practices centred on the transmission of information in favour of practices that help students build knowledge and skills in a more active and responsible way. This study sought to “give students a voice” and, based on a sample of 610 students from the University of A Coruña (Spain), analysed their responses to an open question about how they define teachers who “help them learn”, in particular the characteristics of teachers who explain the curriculum well, or not. Analysis of the the sentences obtained shows that “explaining well” combines clarity, mastery of the subject matter, enthusiasm and empathy on the part of teachers, while “explaining poorly” is associated with a lack of clarity and structure, disinterest, and excessive dependence on or mechanical use of teaching resources. These data show that knowledge of students” perceptions of teaching can guide institutional policies for teacher training and professional development of university lecturers.